From Oppressed to Embraced: The Struggle of Parmalim Adherent In Samosir 1965–2017 - rohinda; pradita, dennys; Pathak, Sunil (Siginjai: Jurnal Sejarah, 2026)
Parmalim is a religious tradition of the Toba Batak people, which continues to thrive in Samosir Regency. This study analyses Parmalim adherents in Samosir Regency during the period 1965–2017 and examines the impact of state policies on the social life and civil rights of this community. The methods employed are historical in nature, comprising heuristics (archival research), oral interviews and a literature review, followed by source criticism, interpretation and the construction of historiography. The research findings indicate that Parmalim adherents have faced administrative obstacles since the implementation of Presidential Decree No. 1 of 1965 and Law No. 23 of 2006, resulting in difficulties in processing civil registration documents (ID cards, family cards, marriage certificates, and birth certificates). Furthermore, the Parmalim community also faces social stigma that views their religious practices as deviant. The struggle of followers of indigenous beliefs reached a crucial juncture with Constitutional Court Ruling No. 97/PUU-XIV/2016, which was delivered in 2017. This ruling opened the way for followers of indigenous beliefs to include their religious identity in civil registration documents